Utilization and Valorization Of Citrus Fruit By-Products: A Review - Siti Amira Othman; Fadzil, Nur Farhana (Enhanced Knowledge in Sciences and Technology, 2021)
Citrus fruits are among the most cultivated fruits around the globe. The production increased due to the rising demands as humans becoming more aware of the health concerns and the nutrients confined in these citrus fruits. Vitamin generated by the juice from citrus-processing industries accounts for almost 50% of the initial fruit mass and the remaining considered underutilized. Hence, these citrus wastes undergoing extraction processes in order to obtain the valuable chemical compounds in the citrus wastes such as pectin, flavonoids, essential oils and phenols as raw materials and sources of energy. The article aims to present the high-value compound in the citrus wastes and their extraction methods for obtaining the value-added products as well as their corresponding applications.